Quatro representações de Zumbi dos Palmares em cordel épico - Mendonça, Luciara Leite de (2018)
Starting from the idea that, in postmodernity, the epic genre receives a new look, which also suggests extension to the string, we will investigate the mythico-historical representation of Zumbi dos Palmares in the face of the dialogue between the epic and the string in the opening of alternatives for the insertion of other discourses (the silenced ones) in History. In view of this, the theme of this work is the study of Zumbi dos Palmares' epic-heroic representation, in cordel, accompanied by reflections on the insertion of this hero in the historiography of the nation and how it appears portrayed in the various literary works. The research aims to focus the historical and mythical treatment given to the heroic figure of Zumbi dos Palmares in string poems that build the representation of this hero, and therefore, are configured as expressions of a popular epic. For this, the discussion will be developed in three stages. In the first stage, we will explore the issues related to the incorporation of Zumbi dos Palmares into historiography. In this stage, we will reflect on the insertion of Zumbi dos Palmares in History (AUGEL, s / a; MOURA, 1972; REIS, 2004; GOMES, 2011; SANTANA, 2012; ARAÚJO, 2015), considering the dislocations of hegemonic discourses. We will reflect, mainly, on the transformations that led the historical discourse to be renewed to recover the forgotten subjects of history, those who came to have the space denied. In the second moment, we will highlight the theoretical aspects about cordel literature and the epic genre. Initially, we consider the study of the theoretical reference contained in History of the Brazilian epic (2007), by AnazildoVasconcelos da Silva and Christina Ramalho, and Christina Ramalho's epic poems: reading strategies (2013) in order to present a synthesis of the the epic theoretical categories formulated to then relate them to the cordel genre itself (Peregrino, 1984, CAVIGNAC, 2006, CURRAN, 2003, LUCIANO, 2012 and ZUMTHOR, 2010). In the last stage, we will analyze the selected works Zumbi, a dream of equality (s / a), by the Sergipe writer JosineideDantas (Gigi), Zumbi dos Palmares Black hero of Brazil (2007) by Fernando Paixão, Zumbi symbol of freedom ) by Antônio Carlos de Oliveira Barreto and Zumbi dos Palmares In Cordel (2013) by Madu Costa, who contemplate the figure of Zumbi dos Palmares, with a view to the confluence between the aesthetic and the ideological. The third moment, therefore, refers to the study of the epic heroism present in the chosen works, since the approach recognizes the double existential condition of the hero: the historical and the mythical. We will take into consideration the following questions: how is Zumbi described?; What historical events are focused ?; How is the insertion of Zumbi in the wonderful plan? Are there differences between the works under the historical record?; How does the narrative voice fit? How is the linguistic apparatus configured in each poem? The final question will be: can each of these string poems be considered a popular epic manifestation?